A comparative study of ultrasound-guided puncture biopsy combined with histopathology and Xpert MTB/RIF in the diagnosis of lymph node tuberculosis - Xiangyu Meng; Hongxiang Fu; Weina Jia; Ying Wang; Gaoyi Yang (Frontiers Media S.A., 2023)
BackgroundCervical tuberculous lymphadenitis (CTBL) is a disease often ignored in clinical work, and pathology and Xpert MTB/RIF (Xpert) are the commonly used methods for tuberculosis diagnosis. This study aimed to compare ultrasound-guided puncture biopsy combined with histopathology and Xpert in the diagnosis of lymph node tuberculosis.MethodsA total of 217 patients highly suspected for CTBL were retrospectively enrolled. All patients underwent ultrasound-guided puncture sampling. All samples were subjected to pathological examination and Xpert test. The sensitivity and specificity of the two methods were compared for all samples. The kappa value was calculated to assess the consistency of the pathological examination and Xpert test using comprehensive diagnosis as the gold standard. Receiver operating characteristic curves of the pathological examination, Xpert test, and their combination were generated, and the areas under the curve (AUCs) were calculated to compare the diagnostic value of the three methods.ResultsThe sensitivity and specificity of the pathological diagnosis of CTBL were 70.1 and 100%, respectively. The sensitivity and specificity of Xpert for CTBL diagnosis were 82.5 and 97.5%, respectively. The results of the pathological examination and Xpert test showed poor consistency in the diagnosis of CTBL, with a kappa value of 0.388. The AUC of the pathological diagnosis of CTBL was 0.850 (95% CI: 0.796-0.895), whereas that of Xpert was 0.900 (95% CI: 0.852-0.936), and the difference was statistically significant (P = 0.0483). The AUC of pathological examination combined with Xpert for the diagnosis of CTBL was 0.956 (95% CI: 0.920-0.979), and the difference between pathological examination combined with Xpert for the diagnosis of CTBL was statistically significant compared with pathological examination and Xpert alone, respectively (both P < 0.001).ConclusionThe diagnostic efficiency of Xpert test is higher than that of pathological examination, but its sensitivity is still not ideal for clinical diagnosis. According to this study, the consistency of Xpert test and pathological diagnosis is poor, and the combination of Xpert test and pathological diagnosis can significantly increase the diagnostic efficiency.